2021
DOI: 10.1177/23733799211045407
|View full text |Cite
|
Sign up to set email alerts
|

Engaging in Anti-Oppressive Public Health Teaching: Challenges and Recommendations

Abstract: Introduction. Public health students are not systematically trained how positionality and power impact public health practice. A grounding in anti-oppression equips practitioners with tools to recognize the impact of present and historical contexts, foster critical self-reflection, and address systems of oppression. The goal of this study was to gather evidence of how anti-oppression is incorporated in public health teaching. Method. Purposive sampling was used to identify public health faculty who engage in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…We recognize the essential value of context in course material and propose to develop country-specific examples and case studies, use local/national/regional statistics, and invite local guest speakers to share their stories. We also believe it is important to incorporate anti-oppressive teaching principles in course delivery mechanisms to address power differentials and colonialism [ 22 ]. This includes co-creation of leadership competencies, materials, and delivery approaches with in-country partners, interactive and equal participation opportunities regardless of social status, regional origin, and culture, as well as opportunities to lead in the local setting.…”
Section: Future Iterations Of the Coursementioning
confidence: 99%
“…We recognize the essential value of context in course material and propose to develop country-specific examples and case studies, use local/national/regional statistics, and invite local guest speakers to share their stories. We also believe it is important to incorporate anti-oppressive teaching principles in course delivery mechanisms to address power differentials and colonialism [ 22 ]. This includes co-creation of leadership competencies, materials, and delivery approaches with in-country partners, interactive and equal participation opportunities regardless of social status, regional origin, and culture, as well as opportunities to lead in the local setting.…”
Section: Future Iterations Of the Coursementioning
confidence: 99%
“… 8 However, research into teaching practices in US schools of public health that declare social justice as part of their mission has shown that AOPs have had limited reach within public health pedagogy to date. 6 Rather, the focus has tended to be on the conceptually more limited notions of equality, equity, and diversity which do not seek systems change but instead focus on increasing individual awareness of differences without giving us tools to change the systems that sustain inequities among us. Even in situations when equity and diversity-related topics emerge in the classroom, faculty tend to avoid these conversations because they feel ill-equipped and hope to evade negative feedback from their students.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous public health studies have documented the impact of threats to belonging—the feeling of being unseen, unwelcome, or unrepresented—not only on academic achievement but also on health itself (Gopalan & Brady, 2020; Paradies et al, 2015). A diverse public health workforce, trained at inclusive institutions of public health, is critical in ensuring anti-racism approaches are amplified and health disparities are effectively addressed (Aqil et al, 2021; Derreth et al, 2021; Goodman et al, 2020; Liburd et al, 2021; Merino, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The creation of a people-centered, inclusive educational climate—one in which not only content but also instructional activities are grounded in evidence-based anti-oppressive practice, is essential to the realization of inclusive institutions (Aqil et al, 2021; Hagopian et al, 2018; Hussain & Jones, 2021; Perez et al, 2021). Anti-oppression is the strategy of mitigating the social harms of those historically oppressed in society and rebalancing power within communities, institutions, and systems.…”
Section: Introductionmentioning
confidence: 99%